DELINEANDO AS FRONTEIRAS DA PSICOLOGIA NO INSTITUTO FEDERAL DO MARANHÃO: UMA ANÁLISE DAS VIVÊNCIAS DAS(OS) PSICÓLOGAS(OS). - ALVES, Vanessa da Silva (2019)
The professional performance of Psychology in the Federal Institutes of Education, Science and Technology has been mostly associated in literature to School and Educational Psychology with critical bias. However, research also demonstrates that the experience of each of the 453 psychologists currently working in brazilian Federal Institutes of Education is marked by both the plurality of practices and the unique appropriation that each professional makes of psychological theories. The present research had the main objective to analyze the professional performance of Psychology in the Federal Institute of Maranhão (IFMA), from its psychologists' experiences. To this end, the research proposed three specific objectives: describing the constitution of IFMA's Psychology Service; identifying the General Descriptive Structure of Senses related to the practice of the Psychology professional currently working in IFMA; and understanding the experience of being a psychologist at IFMA based upon the experience of professionals. For that matter, the methodological design of Amedeo Giorgi's Phenomenology subsidized the investigation of experiences through individual interviews. Nine professionals working on different IFMA campuses collaborated with this research. In the end, this research identified four structuring axes for phenomenon analysis of Psychology's professional performance in the IFMA: the Context of Professional, Scientific and Technological Education in Maranhão; the Psychology Practices at the Federal Institute of Maranhão; the Identity of IFMA's Psychology professional; and Institutional Relations and Affectivity. In addition, it identified twenty-five units of meaning related to the four aforementioned axes. This research demonstrated that the History of the Psychology Service at IFMA has been constituted since the late nineties, through professional practice characterized by the plurality of practices. For this matter, the experience of professionals reveals the discovery of the School Psychologist's place in the institution from a gradual process of professional identity construction. Thus, the professional performance of the Psychology Service at IFMA is delineating its boundaries based on demarcation of a territory of permeable and flexible practices, which are updated according to institutional demands.